British Association of Sport and Exercise Sciences
British Association of Sport and Exercise Sciences (BASES) is the UK professional body for all those with an interest in the science of sport and exercise. http://www.bases.org.uk contains latest news stories and major events, ensuring that visitors have easy access to information regarding the BASES workshop programme as well as the BASES annual and student conferences. Other features include a bulletin board, job vacancies, education and links. There are also dedicated content areas on Accreditation and Supervised Experience. BASES` strong support of students is also reflected, with dedicated content areas for students, focusing on undergradaute, postgraduate and career information.